DISTRIBUTION PATTERN FOR HLA SPECIFICITIES IN THE PATIENTS WITH ACUTE MYELOID LEUKEMIA - I. R. Ramilyeva; Zh. K. Burkitbaev; S. A. Abdrakhmanova; A. A. Turganbekova; D. K. Baimukasheva; E. B. Zhiburt (Медицинская иммунология, 2019)
The article presents a study on the distribution of gene polymorphisms in the histocompatibility antigens among the patients diagnosed with AML, and healthy donors in the Republic of Kazakhstan, as well as features of the HLA-A*, *B, Cw*, DRB1*, DQB1* distribution among the patients with acute myeloid leukemia (AML). HLA typing and data processing were performed at the Research and Production Center of Transfusiology, Nur-Sultan. A total of 3808 people were examined, including 3621 healthy blood donors and 187 patients diagnosed with AML. Genomic DNA for HLA typing was isolated from peripheral blood leukocytes by proteinase method using columns with silica membrane and using a set of reagents PROTRANS DNA BOX (Protrans, Germany). Typing of HLA-A, B, C, DRB1, DQB1 in the patients and blood donors was performed by polymerase chain reaction using commercial reagent kits from Protrans (PROTRANS HLA- A*/B*/DRB1* Cyclerplate System, PROTRANS HLA-C* Cyclerplate System, PROTRANS HLA-DQB1* Cyclerplate System).HLA-A*31 (OR = 1.8; CI 1.16-2.79; p < 0.01) proved to be more common in the group of patients compared to the control group, which suggesting an association between AML and presence of this antigen. The control group showed an increased frequency of HLA-A*02 antigen (OR = 0.55; CI 0.41-0.75; p < 0.01). This antigen may be, therefore, exert a protective effect in AML development.The studies of major histocompatibility complex which include HLA genes, did significantly expanded the understanding of HLA antigens which may have strong associative links with distinct diseases, and moderately or poorly expressed links in other disorders. Analysis of the literature data showed that myeloid leukemia is characterized by decreased frequency of HLA-B13, B14, B40 antigens, most often determined by antigens B16, Bw 22, B27. In this study, HLA-A*31, B*37 were associated with AML. Phenotypes with antigens HLA-A*02, B*27, C*02, DRB1*01, *04, DQB1*06 have a probable protective effect on the development of this pathology.The study has determined some features of histocompatibility gene distribution in AML patients, detection of HLA-markers that determine the risk or resistance to the occurrence of this disease. We have established characteristic specific markers of HLA system among AML patients in Kazakhstan, which may be associated with higher risk of the disease.